Case Report: Diabetes mellitus type MODY5 as a feature of 17q12 deletion syndrome with diabetic gastroparesis - Xin, Sixu; Zhang, Xiaomei (Frontiers in Endocrinology, 2023)
Background Maturity-onset diabetes of the young type 5 (MODY5) is an uncommon, underrecognized condition that can be encountered in several clinical contexts. It is challenging to diagnose because it is considered rare and therefore overlooked in the differential diagnosis. Moreover, no typical clinical features or routine laboratory tests can immediately inform the diagnosis. Case presentation We report a 28-year-old man who was once misdiagnosed with type 1 diabetes due to decreased islet function and recurrent diabetic ketosis or ketoacidosis. However, he had intermittent nausea, vomiting, abdominal distension, and abdominal pain 6 months prior. Further examinations revealed agenesis of the dorsal pancreas, complex renal cyst, kidney stone, prostate cyst, hypomagnesaemia, and delayed gastric emptying. Accordingly, whole-exon gene detection was performed, and a heterozygous deletion mutation was identified at [GRCh37 (hg19)] chr17:34842526-36347106 (1.5 Mb, including HNF1B gene). The patient was eventually diagnosed with 17q12 deletion syndrome with gastroparesis. Conclusion We report a novel case of diabetes mellitus type MODY5 as a feature of 17q12 deletion syndrome caused by a new 17q12 deletion mutation, which will further broaden the genetic mutation spectrum of this condition. With the help of gene detection technology, these findings can assist endocrinologists in making the correct diagnosis of MODY5 or 17q12 deletion syndrome. Additionally, they can formulate an appropriate therapy and conduct genetic screening counseling for their family members to guide and optimize fertility.